Clean Water Treatment for Public Health in Indonesia: A Review - Yusuf Lateke, Ahmad Tirta; Maharani, Aprilia Dwi; Restandi, Windi (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Clean water is an essential need that directly impacts public health. Poor water quality can lead to disease, making water treatment a valuable solution to ensure safe access to clean water. Various treatment methods have been developed, ranging from simple technologies to modern, environmentally friendly approaches. Objective: This study aims to identify and analyze the effectiveness of various clean water treatment methods based on current literature, and to provide recommendations for the implementation of good technology. Methods: The method used was a literature review by searching for scientific articles through the Google Scholar portal and related databases. Specific criteria: publications between 2021 and 2025, in Indonesian and English, full text , and with a DOI. The analysis was conducted on articles relevant to the keywords water treatment, technology, coagulation, flocculation, sedimentation, filtration, and disinfection. Results: This study showed that coagulation-flocculation was effective in reducing BOD, COD, and turbidity in textile wastewater. Filtration with raw wood activated charcoal was more effective than other media in reducing the turbidity of dug well water. Disinfection with ozone successfully eliminated Escherichia coli bacteria up to 100%, while the combination of aeration-filtration could significantly reduce Fe levels. Conclusion: Water treatment technologies such as filtration, coagulation, and disinfection are quite effective in improving water quality, despite limitations in infrastructure and public awareness. Implementing effective technology and promoting sustainable water treatment are key to ensuring access to clean water in Indonesia. Keywords: Escherichia coli, Wastewater, Water Quality, Indonesia, Charcoal